(untitled) (Revista Argentina de Cirugía, 2026)
Background: The incidence of colorectal cancer (CRC) is increasing in people < 50 years, a group that has traditionally been excluded from screening programs and is characterized by the presence of more aggressive tumors. This trend poses diagnostic, therapeutic, and social challenges. Objectives: The aim of this study was to compare the characteristics of patients aged 50 or younger versus those over 50 who underwent surgery for CRC. Material and methods: We conducted a cross-sectional, analytical and retrospective study. The following variables were recorded: demographic data, American Society of Anesthesiologists (ASA) physical status classification, and histopathological and therapeutic characteristics of patients undergoing CCR surgery between January 2019 and December 2024. The variables were compared using Pearson’s chi-square test or Fisher’s exact test. Results: A total of 155 patients were included and assigned to two groups: those ≤ 50 years (n = 36) and those > 50 years (n = 119). Younger patients exhibited a higher proportion of men (p = 0.016), cases classified as ASA grade 1 (p = 0.004) and rectal cancer (p = 0.026). There were no significant differences in the histological characteristics, recurrence rate (p = 0.407), or overall mortality (p = 1.0). There was a non-significant trend among young patients to present poorly differentiated tumors (11.1% vs. 6.7%; p = 0.202) and to receive chemotherapy at stage II (30% vs. 15%; p = 0.358). Conclusion: Patients aged 50 years or younger showed differences in demographics, ASA physical status classification, and tumor location